Predictive Maintenance of Cooling System in Casting Process by Data SCADA - Engelbert Harsandi Erik Suryadarma, The Jin Ai, Brilianta Budi Nugraha (International Journal of Advanced Science and Technology, 2020)
In the casting process, cooling system is very important. Without a good cooling system, the casting process will be very long time and the process of solidification becomes uncontrolled. This paper presents a comprehensive predictive maintenance system for the cooling system of the die casting process. This predictive maintenance system is created in order to ensure the cooling system remained in good condition throughout the process. It is built based on the SCADA system combined with data mining technique, which is linear regression algorithm combined with rule based classification. We use prototype of casting processes on a laboratory scale in order to test this system.